Co-designing with people living with dementia. Issue 3 (3rd July 2018) - Rodgers, Paul A.
Abstract: This paper presents research that illustrates how design thought and action has contributed to the co-design and development of a mass-produced product with people living with dementia. The research, undertaken in collaboration with Alzheimer Scotland, has adopted a range of disruptive design interventions for breaking the cycle of well-formed opinions, strategies, mindsets, and ways-of-doing, that tend to remain unchallenged in the health and social care of people living with dementia. The research has resulted in a number of co-designed interventions that will help change the perception of dementia by showing that people living with dementia can offer much to UK society after diagnosis. Moreover, it is envisaged that the co-designed activities and interventions will help reconnect people recently diagnosed with dementia to help build their self-esteem, identity and dignity and help keep the person with dementia connected to their community, thus delaying the need for formal support and avoid the need for crisis responses. The paper reports on an initial intervention where the author worked collaboratively with over 130 people diagnosed with dementia across Scotland in the co-design and development of a new tartan. The paper concludes with a number of recommendations for researchers when co-designing with people living with dementia.